Apathetic apps: mobile application development to lock smartphones and unlock it by user’s conversation / Fadhil Arif Muhammad ... [et al.] - Muhammad, Fadhil Arif; Putra, Dimi Karillah; Haikal, Raihan; Thohir Wijaya, Raden Abdurrohman; Kurniawan, Edy (Universiti Teknologi MARA, Kedah, 2019)
Smartphones allow people to connect with everyone from almost anywhere at any time. However, there are a few act in using smartphones that can damage people’s social relations for instance “phubbing”. The terms “phubbing” means the act of ignoring another people by focusing on one’s phone. According to a few researches that has been conducted, phubbing can damage the relationship between someone and their interlocutor. “(A)pathetic Apps” is an mobile application designed with the intent to reduce the act of “phubbing” by locking the user’s smartphone and ask for words to be spoken so the user can unlock their smartphone again. This application makes the user not able to use their smartphone for a while and force them to join the conversation that is happening in front of them. “(A)pathetic Apps” can be a solution for problems that are going to surface because of the phubbing act conducted by people to their surroundings. Reduction in smartphones addiction allow people to connect even more with everyone surrounding them. Application that is making the user put down their smartphone still has not many competitors. This application can be a leading application in their category because the offered solution can help people put down their smartphone even just for a while.